Effect of Addition of Urea and Zeolite on Rice Plants (Oryza sativa L.) to Nitroxy Emissions on Peatlands - Asia Asia Afriyani; Muhammad Bambang Prayitno; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The purpose of this study is to analyze nitro oxide emissions as a result of adding urea and zeolite to rice plants (Oryza sativa L.) on peatlands. The treatments used were 2 factors, namely factor 1 using a dose of urea fertilizer from three levels of treatment N1 : 125 kg/ha; N2 : 250 kg/ha; N3 : 375 kg/ha and factor 2, the dose of zeolite consists of three levels of treatment Z1 : 125 kg/ha; Z2 : 250 kg/ha; Z3 : 375 kg/ha. Each combination was repeated as many as 5 phases (phase 1 = 15 DDP, phase 2 = 35 DDP, phase 3 = 55 DDP, phase 4 = 65 DDP and phase = 90 DDP) so the number of units treatment 3 x 3 x 5 = 45 pots. Data analysis used linear regression test. The results showed the administration of a combination of urea doses and zeolite in rice plantations had not significant effect on nitrous oxide emissions produced at each observation. In this study, the highest nitrous oxide emissions were obtained in phases 1 and 2. From the results of the F test is Ho rejected. With this it is proven that the urea dose partially has not significant effect on nitro oxide emissions. The dose of zeolite (X2) is H0 is rejected, thus showing that zeolite has not significant effect on the availability of nitrous oxide emissions.Keywords: Urea, Zeolite, Nitro oxide emissions peatlands